Innovation Strategy of SMA Batik 1 Surakarta in Developing Adiwiyata on Limited Green Land - Putri, Nur Aliya Widya; Puspita, Putri Dian; Salma, Talitha Nabilah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
SMA Batik 1 Surakarta developed an adiwiyata program despite having limited green space. In a dense urban context with minimal open space, this school is able to prove that physical limitations do not hinder commitment to environmental education. Through a descriptive qualitative approach, data were obtained from in-depth interviews, observations, and documentation of teachers and students. The results showed that the school implemented various innovative, creative strategies, such as vertical gardens from recycled plastic bottles, utilization of used ablution water for the eco mapping program every Friday. These activities actively involve students in structuring the school environment and greening efforts, in line with the participatory and sustainable principles in Adiwiyata as well as strengthening the character values of Pancasila students. Environmental values are also integrated in subjects such as Biology and Sociology, and extended to the community through the distribution of plant seeds. School members as agents are able to produce and develop environmental education structures creatively and reflectively. The success of the Adiwiyata program is not determined by land area, but by the synergy between agents and structures that encourage the creation of an ecological and sustainable school culture. This research is an important reference for urban schools facing similar challenges.SMA Batik 1 Surakarta developed an adiwiyata program despite having limited green space. In a dense urban context with minimal open space, this school is able to prove that physical limitations do not hinder commitment to environmental education. Through a descriptive qualitative approach, data were obtained from in-depth interviews, observations, and documentation of teachers and students. The results showed that the school implemented various innovative, creative strategies, such as vertical gardens from recycled plastic bottles, utilization of used ablution water for the eco mapping program every Friday. These activities actively involve students in structuring the school environment and greening efforts, in line with the participatory and sustainable principles in Adiwiyata as well as strengthening the character values of Pancasila students. Environmental values are also integrated in subjects such as Biology and Sociology, and extended to the community through the distribution of plant seeds. School members as agents are able to produce and develop environmental education structures creatively and reflectively. The success of the Adiwiyata program is not determined by land area, but by the synergy between agents and structures that encourage the creation of an ecological and sustainable school culture. This research is an important reference for urban schools facing similar challenges.